Kedudukan dan Fungsi Lembaga Kemasyarakatan Desa di Desa Buar Kecamatan Rahong Utara Kabupaten Manggarai Berdasarkan Peraturan Menteri dalam Negeri Nomor 18 Tahun 2018 Tentang Lembaga Kemasyarakatan Desa dan Lembaga Adat Desa - Hendrikus Bagut Jemarung; Yohanes G Tuba Helan; Cyrilius W. T Lamataro (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
This study analyzes the position and function of village community institutions in Buar Village, North Rahong District, Manggarai Regency based on Permendagri No. 18 of 2018. The method used in this study is an empirical judiciary method using primary data and secondary data. Law of the Republic of Indonesia Number 23 of 2014 (Law No.23 of 2014) concerning Regional Government states that in the village a community institution can be established stipulated by Village Regulations guided by Laws and Regulations. In the general explanation of the Law, it is explained that in order to realize democratization and transparency of development at the community level and to encourage, motivate, and create access so that the community plays a more active role in development activities as well as assisting the village government in managing development and community empowerment, it is necessary to establish community institutions in the village. The formulation of the problem in this study is: (1) What is the position of Village Community institutions in Buar Village, North Rahong District, Manggarai Regency Based on the Regulation of the Minister of Home Affairs Number 18 of 2018?, and (2) Factors Hindering the Implementation of the Authority of the Position of Village Community Institutions in Buar Village, North Rahong District, Manggarai Regency Based on the Regulation of the Minister of Home Affairs Number 18 of 2018?. From the results of the research, the author concludes that the function of community institutions in the implementation of development in Buar Village, North Rahong District, Manggarai Regency has not been maximized in accordance with the Regulation of the Minister of Home Affairs Number 18 of 2018. Some of the functions that have not been implemented include the preparation of development plans in a participatory manner, the shelter and distribution of community aspirations, and the increase of community participation in development. Factors inhibiting the implementation of the authority of Village Community institutions include lack of resources, limited knowledge and skills of village institution members, dependence on the central or regional government, corruption and nepotism practices, internal conflicts, and leadership instability.